Gender Inequalities in Everyday Life - Chhabra S (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2015)
Background: Gender inequalities continue in all walks of life for all women, urban rural. Objective: was to know gender differences in everyday life of women. Material methods: Thousand non-pregnant and thousand, pregnant women were interviewed. Results: The information revealed that around 90% pregnant, nonpregnant women, 25% men went to bed late, got up early. Women did all household chores, without any help from husbands. Grocery was brought by 269 nonpregnant, 78 pregnant women. Firewood was collected by 58% woman of 575, households where firewood was used 45% of 513 pregnant women's families. Of women who worked outside 61% of 656 nonpregnant, 93% of 353 pregnant did all household work also Age, education, occupation did not make any difference in gender inequality of everyday life. Conclusion: All household chores are performed only by women even during pregnancy also, with some difference during pregnant state from nonpregnant. Less pregnant women worked outside, but those who worked did all household work also. Perception that men do outside jobs, women only household, was not true.